The Negotiation Stage: Decision Process of Public Service Innovation for Community Complaints in Pekanbaru - Handrian, Eko; Putera, Roni Ekha; Asrinaldi, Asrinaldi; Zetra, Aidinil (Jurnal Manajemen Pelayanan Publik, 2024)
The diffusion of innovations in public service contexts regularly involves various yet complex challenges that require a deep understanding of the dynamics of the adoption, spread, and application of new ideas. Persuasion may no longer be fully expected to influence the adoption of innovation, so this article aims to analyze negotiation as an important part of the innovation-decision process for public complaint services in Pekanbaru (city). This research applies qualitative methods with data collection techniques through interviews, documentation, and observation. All data that have been collected are then analyzed through data reduction, data presentation, and data conclusions. The research results show that the negotiation stage is an important part of the innovation decision process, negotiation is a key element in facilitating the adoption of innovation in the context of public services, through negotiation stakeholders can interact with each other and reach agreement. Conflicts of interest, sectoral egos, and limited resources make negotiation important in the innovation diffusion stage of the innovation-decision process to create agreement and sustainability.